Biodegradation of dinitrotoluene sulfonates and other nitro-aromatic compounds by Pseudomonas sp. X5 isolated from TNT red water contaminated soil. (20th March 2019) - Xu, Wenjie; Zhao, Quanlin; Li, Zhilin; Lu, Xinyue; Han, Shiqun; Ye, Zhengfang
Abstract: A dinitrotoluene sulfonates degrading bacterium strain Pseudomonas sp . X5 was isolated from 2, 4, 6-trinitrotoluene red water contaminated soil in Gansu, China, which was used for biodegradation of dinitrotoluene sulfonates. The growth experiments were carried out to optimize the growth condition of X5. Effect of inoculation amount was investigated. Plasmid curing tests were conducted to determine whether the dinitrotoluene sulfonates degrading gene is chromosomal or plasmid encoded. The results showed that the optimum growing conditions for X5 were 35 °C, pH 7–9 and 1% (salinity). The biodegradation rates of dinitrotoluene sulfonates were highly affected by inoculation amount. When the inoculation amount was 25%, 100% of 2, 4-dinitrotoluene-3-sulfonate and 2, 4-dinitrotoluene-5-sulfonate could be biodegraded. Liquid chromatography-mass spectrometry analysis showed that the nitro groups in dinitrotoluene sulfonates were transformed to amino groups. Pseudomonas sp. X5 has broad-spectrum degradation characteristics. It can degrade not only dinitrotoluene sulfonates, but also other nitro-aromatic pollutants like 2, 4, 6-trinitrotoluene, dinitrotoluene and mononitrotoluene. The ability of Pseudomonas sp . X5 to degrade dinitrotoluene sulfonates, was found to be plasmid encoded. The size of the relevant plasmid was estimated to be about 20 kb. Graphical abstract: Highlights: A Pseudomonas sp. X5 which can degrade dinitrotoluene sulfonates was isolated. Degradation pathways of two dinitrotoluene sulfonates were proposed. The degradation spectrum of X5 was investigated. The degradation gene was founded to be plasmid encoded.